carnivalesque retrieval in living doll self-display - Shiva Massoudi; Nafiseh Saadat (زن در فرهنگ و هنر, 2022)
“Living doll” is a term for young girls who transform themselves into toy dolls like Barbie with surgery and heavy makeup, and display their gestures and behaviors on social media by posting photos or videos. In this article, by producing a readout of carnival and carnivalesque from the perspective of Bakhtin, death, mask, madness (manifested in three types of rogue, clown, fool) and play are introduced and identified as its four main themes. The background of the research shows that the embodiment of these themes in literary works or social and political phenomena can lead to the development of carnivalesque. In search of carnival elements in Living doll term, we come to the virtual space as the carnival square. Cyber display has two parts, one is its representation, which from Goffman's point of view has an executive aspect, and the second is the place of its performance in cyberspace and specifically social networks; Where it allows each person to create different, artificial and ideal identities. The living doll, which has a history in literary sources as well as in girls' desire to imitate dolls, puppets or cartoon characters, is the choice of a strange puppet-like identity in cyberspace. living dolls embody the four themes of carnival with concepts of inanimate being and mortality, face and body masks, stupidity, rebellion, deception and wondering, and acting as puppets. And in this way, they turn their cyberspace show into a carnival from Bakhtin's point of view.